FEAR OF MISSING OUT (FOMO) AS A CONSUMPTION DETERMINANT IN THE DIGITAL ECONOMY AMONG AKABA CADETS: Fear of Missing Out (FOMO) sebagai Consumption Determinant dalam Ekonomi Digital di Kalangan Taruna AKABA - Purnama, Jovie Candra; Geri Damayanto (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
The escalation of the digital economy has reconstructed the consumption patterns of the younger generation, particularly through the psychological influence of Fear of Missing Out (FOMO). This qualitative study aims to explore the determinants of impulsive buying behavior among AKABA Cadets, a unique social group within a semi-military educational environment. Utilizing purposive sampling of 10 respondents, data were analyzed thematically through systematic reduction and categorization. The findings confirm that TikTok dominates consumption exposure at 60%, where social media algorithms trigger a purchase desire of up to 90% through scarcity marketing strategies. There is a significant disconnection between cognitive awareness of negative financial impacts and behavioral control; impulsive purchases are still executed to mitigate the risk of digital social isolation. This study fills a literature gap by shifting the focus from general consumers (the broader Gen Z) to a specific social group within a disciplined educational institution, a unique cultural environment previously under-explored in the context of the digital economy. Theoretically, this research maps the interaction between psychological determinants and the disciplinary structure of vocational education. It concludes that FOMO functions as a psychological consumption trigger capable of overriding economic rationality. The practical implications emphasize the urgency of strengthening financial and digital literacy as instruments to mitigate consumptive behavior within maritime educational institutions.